2020
DOI: 10.1186/s40644-020-00312-3
|View full text |Cite
|
Sign up to set email alerts
|

What scans we will read: imaging instrumentation trends in clinical oncology

Abstract: Oncological diseases account for a significant portion of the burden on public healthcare systems with associated costs driven primarily by complex and long-lasting therapies. Through the visualization of patient-specific morphology and functional-molecular pathways, cancerous tissue can be detected and characterized noninvasively, so as to provide referring oncologists with essential information to support therapy management decisions. Following the onset of stand-alone anatomical and functional imaging, we w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 238 publications
(251 reference statements)
0
24
0
Order By: Relevance
“…In oncology, imaging methods have become an indispensable part of the diagnostic approach [5]. The conventional imaging modalities, such as X-ray imaging, computed tomography (CT), and magnetic resonance imaging (MRI), established in cancer management, are usually followed by invasive biopsy extraction for a definite diagnosis [6]. Molecular imaging, which provides valuable insight into biological processes at cellular and sub-cellular levels, has exhibited the potential to suppress such an invasive procedure [7].…”
Section: Introductionmentioning
confidence: 99%
“…In oncology, imaging methods have become an indispensable part of the diagnostic approach [5]. The conventional imaging modalities, such as X-ray imaging, computed tomography (CT), and magnetic resonance imaging (MRI), established in cancer management, are usually followed by invasive biopsy extraction for a definite diagnosis [6]. Molecular imaging, which provides valuable insight into biological processes at cellular and sub-cellular levels, has exhibited the potential to suppress such an invasive procedure [7].…”
Section: Introductionmentioning
confidence: 99%
“…cadmium-zinc-telluride) for SPECT with high performance diagnostic CT scanners. Statistical iterative image reconstruction algorithms have been implemented for SPECT and several vendors offer CT-based attenuation, scatter and even motion correction techniques for improved quantification [18]. Of note, one vendor provides a tri-modality SPECT-CT-PET system for maximum versatility [60].…”
Section: Combined or Hybrid Imaging And Related Physicsmentioning
confidence: 99%
“…Imaging is a means, provided through technological and methodological advances, to view the human body from outside and inside, to probe anatomical, functional and even molecular and signaling pathways non-invasively for new information of the state of the patient for rendering an accurate and personal diagnosis. Medical imaging, by means of radiology and molecular imaging, has become a foundation for diagnosis and therapy planning in numerous diseases that patients present with [18]. What is more, imaging is being used extensively in healthy subjects, or volunteers to better understand physiology and signaling, for example in the brain, so as to build reference models of normal physiology, biology and functional correlates that can be employed to better define abnormal variants during diagnostic and therapeutic work-up of patients.…”
mentioning
confidence: 99%
“…The increase in knowledge in oncology and the possibility of creating personalized medicine by selecting a more appropriate therapy related to the different tumor subtypes, as well as the management of patients with cancer within a multidisciplinary team has improved the clinical outcomes [ 1 ].…”
mentioning
confidence: 99%
“…The characteristics involved are a more appropriate surveillance for the patient at risk to obtain an early diagnosis of the disease, an improvement in the efficacy of therapies based on better patient selection [ 1 , 2 ] and, thanks to a more strategic approach, the possibility of identifying responders or non-responders to therapies as soon as possible, not least the possibility of selecting different treatments related to genomic data. In fact, it has been shown that genomic markers such as microRNA expression are associated with the response to treatment, metastatic spread and prognosis that could offer personalized and precision medicine.…”
mentioning
confidence: 99%